Mechanics of Biomaterials (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The mechanical behavior of biomedical materials and biological tissues are important for their proper function. This holds true, not only for biomaterials and tissues whose main function is structural such as skeletal tissues and their synthetic substitutes, but also for other tissues and biomaterials. Moreover, there is an intimate relationship between mechanics and biology at different spatial and temporal scales. It is therefore important to study the mechanical behavior of both synthetic and livingbiomaterials. This Special Issue aims to serve as a forum for communicating the latest findings and trends in the study of the mechanical behavior of biomedical materials.